Nutritional evaluation of bird's diet - focus on frugivorous birds - Rabiatul Adawiyah, Bt. Mohd Aris (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Wild fruits provide nutrients and energy for wild animals. However, information on nutrition value of wild fruit is not uch study compared to the domestic fruit. This research evaluated on nutrients content in fruit which birds consumed fruits as It food resource. This study was conducted at Bukit Sewa, Padawan and Unimas. Bpkit Sewa is an example of limestone forest which is very unique and diverse in habitat and numerous of flora and fauny This study was carried out by identifying species of birds that feed on fruit tree species. From Padawan fieldwork observations, Passer montanus, Ficedula wastermanni, Treron olax, Pycnonotus brunneus, D.c.nigrimenenum, Treron vernans, Dicaeum cruentatum, and Arachnot)Jera longirostra was recorded consumed, on fruits. Five species of fruit consumed by frugivorous birds are Ficus sp. Durio sp, Theobroma sp and two species of fruits from family Loranthaceae and Melastomataceae. While in Unirnas. Prionochilus maculates. Treron vernans, and Anthreptes simplex was recorded consumed on Ficus benjamina. Ficus sp recorded the highest of individuals birds consuming it fruits, 15 individuals of birds which are 7 individuals of Passer mont anus, 3 individuals of Ficedula wastermanni, 2 individuals of Treron olax, and 3 individuals of Pycnonotus brunneus. Ficus sp contain highest nutrients which are 80.57% of water content, 3.62% of ash, 24.62% of crude fiber, 6.32% ofcrude protein, 7.60% of ether extracts, 57.84% of (Nitrogen Free Extracts) NFE, 4.87 mg/g of calcium and 1.82 mg/g ofphosphorus.